Structure of snow-ice dams of the outburst lakes in the Broknes Peninsula (Larsemann Hills, East Antarctica) based on groundpenetrating radar data - S. Grigoreva D.; E. Kiniabaeva R.; M. Kuznetsova R.; S. Popov V.; M. Kashkevich P.; С. Григорьева Д.; Э. Киньябаева Р.; М. Кузнецова Р.; С. Попов В.; М. Кашкевич П. (Ice and Snow, 2021)
During the summer ﬁeld season of the 65th Russian Antarctic Expedition a research aimed at studying the structure of the snow-ice dams of the Lakes Progress and Discussion (Larsemann Hills, East Antarctica), which are characterized with annual outburst ﬂoods, was carried out. Survey was performed using groundpenetrating radar sounding complemented with noncore drilling and analysis of the aerial photo data acquired with unmanned aerial vehicle during the last ﬁeld seasons. The results show that location of the waterways, which occur during the outbursts of the both lakes, does not change signiﬁcantly year in year out and ﬁts a linear depression in basement topography under the dam and a following ﬂexure of the ice layer. During the winter period, the opened channels are being ﬁlled with snow, and thereby a natural soﬅened zone is being formed. Further outburst ﬂood propagates mainly within this zone. Monitoring survey of the snowi-ce dam of the Progress Lake during the summer period showed that destruction of the dam does not happen rapidly when the outburst takes place, but begins a few weeks before it with gradual ﬁltration within the snow layer. Приведены результаты изучения строения снежно-ледовых перемычек прорывоопасных озёр Прогресс и Дискашн (оазис Холмы Ларсеманн, Восточная Антарктида), выполненные методом георадиолокации. Дополнительно проведены бескерновое механическое бурение и аэрофотосъёмка с использованием беспилотного летательного аппарата. На примере изученных водоёмов установлены основные геолого-гляциологические тенденции формирования прорывных паводков ледниковых озёр.